2020
DOI: 10.31234/osf.io/5b7y2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The use of immersive 360° videos for foreign language learning: a study on usage and efficacy among high-school students

Abstract: The large-scale diffusion of tablets and smartphones in the last decades offered new opportunities to broaden educational strategies. In particular, the Mobile-Assisted Language Learning (MALL) emerged as a promising approach leveraging the widespread availability of portable devices. In this study we investigated the feasibility and efficacy of a self-administered MALL homework training based on immersive 360° videos, compared to a training based on not-immersive standard videos showing the same visual conte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Students totally agreed that video-360 provided a positive experience for Indonesian language learning. A positive attitude toward technology watched the videos more than those with a less positive attitude (Repetto et al, 2021). The data also explained that the video-360 was a device that had a potential role to elevate learners' keenness to learn the Indonesian language in the Polytechnic education system.…”
Section: Resultsmentioning
confidence: 92%
“…Students totally agreed that video-360 provided a positive experience for Indonesian language learning. A positive attitude toward technology watched the videos more than those with a less positive attitude (Repetto et al, 2021). The data also explained that the video-360 was a device that had a potential role to elevate learners' keenness to learn the Indonesian language in the Polytechnic education system.…”
Section: Resultsmentioning
confidence: 92%
“…However, further research is needed to investigate how the peculiarity of immersive systems could affect the learning affordances, compared to less immersive ones. Recently, Repetto et al (2020, June 3) manipulated the immersive feature of VR and compared the efficacy of a self-administered language learning training based on immersive 360° videos with the same training based on non-immersive standard videos. Results showed that students trained with immersive 360° videos learned more than students belonging to the control group.…”
Section: Practical Implications and Conclusionmentioning
confidence: 99%
“…360-degree video has been extensively employed in VR systems for training decision making in sports [4,8], learning foreign languages [11], medical education [9], pedagogy [2]. VR systems presenting audiences in pre-recorded 360 videos were also shown to be an effective training tool for reducing anxiety in public speaking [12].…”
Section: Related Work 21 Vr Training Environmentsmentioning
confidence: 99%